Safety, efficacy, and tolerability of memantine for cognitive and adaptive outcome measures in adolescents and young adults with Down syndrome: a randomised, double-blind, placebo-controlled phase 2 trial. Issue 1 (January 2022) - Costa, Alberto C S; Brandão, Ana C; Boada, Richard; Barrionuevo, Veridiana L; Taylor, Hudson G; Roth, Elizabeth; Stasko, Melissa R; Johnson, Mark W; Assir, Fernanda F; Roberto, Maria P; Salmona, Patrícia; Abreu-Silveira, Guilherme; et al.
Summary: Background: Down syndrome is a chromosomal disorder with considerable neurodevelopmental impact and neurodegenerative morbidity. In a pilot trial in young adults with Down syndrome, memantine (a drug approved for Alzheimer's disease) showed a significant effect on a secondary measure of episodic memory. We aimed to test whether memantine would improve episodic memory in adolescents and young adults with Down syndrome. Methods: We did a randomised, double-blind, placebo-controlled phase 2 trial with a parallel design, stratified by age and sex. Participants (aged 15–32 years) with either trisomy 21 or complete unbalanced translocation of chromosome 21 and in general good health were recruited from the community at one site in Brazil and another in the USA. Participants were randomly assigned (1:1) to receive either memantine (20 mg/day orally) or placebo for 16 weeks. Computer-generated randomisation tables for both sites (allocating a placebo or drug label to each member of a unique pair of participants) were centrally produced by an independent statistician and were shared only with investigational pharmacists at participating sites until unblinding of the study. Participants and investigators were masked to treatment assignments. Neuropsychological assessments were done at baseline (T1) and week 16 (T2). The primary outcome measure was change from baseline to week 16 in the California Verbal Learning Test–second edition short-form (CVLT-II-sf) total free recall score, assessed in the per-protocol population (ie, participants who completed 16 weeks of treatment and had neuropsychological assessments at T1 and T2). Linear mixed effect models were fit to data from the per-protocol population. Safety and tolerability were monitored and analysed in all participants who started treatment. Steady-state concentrations in plasma of memantine were measured at the end of the trial. This study is registered at ClinicalTrials.gov, number NCT02304302 . Findings: From May 13, 2015, to July 22, 2020, 185 participants with Down syndrome were assessed for eligibility and 160 (86%) were randomly assigned either memantine (n=81) or placebo (n=79). All participants received their allocated treatment. Linear mixed effect models were fit to data from 149 (81%) participants, 73 in the memantine group and 76 in the placebo group, after 11 people (eight in the memantine group and three in the placebo group) discontinued due to COVID-19 restrictions, illness of their caregiver, adverse events, or low compliance. The primary outcome measure did not differ between groups (CVLT-II-sf total free recall score, change from baseline 0·34 points [95% CI –0·98 to 1·67], p=0·61). Memantine was well tolerated, with infrequent mild-to-moderate adverse events, the most common being viral upper respiratory infection (nine [11%] participants in the memantine group and 12 [15%] in the placebo group) and transient dizziness (eight [10%] in the memantine group and six [8%] in the placebo group). No serious adverse events were observed. Amounts of memantine in plasma were substantially lower than those considered therapeutic for Alzheimer's disease. Interpretation: Memantine was well tolerated, but cognition-enhancing effects were not recorded with a 20 mg/day dose in adolescents and young adults with Down syndrome. Exploratory analyses point to a need for future work. Funding: Alana Foundation. Translation: For the Portuguese translation of the abstract see Supplementary Materials section.